Correlation Between Third Molar Agenesis and Particular Dental Conditions - Loredana Golovcencu; Gabriela Geletu (Romanian Society of Oral Rehabilitation, 2012)
The aim of this study was to investigate the frequency of dental anomalies in orthodontic patients with third molar agenesis, comparing them with patients without third molar agenesis. A sample of 250 patients, aged between 11 and 25 years was taken into study. Panoramic radiographs and dental casts were used to determine associated dental anomalies, such as third molar agenesis, hypodontia, impaction and delayed formation and eruption of the permanent teeth. The Pearson chi-square and Fisher exact test were used to determine the distribution and the relation between third molar agenesis and other dental anomalies. The prevalence of other teeth agenesis was 11.4% of all subjects with third molar congenitally missing, compared with 7.8% of subjects with all third molars present. The frequency of cases with delayed eruption of the dentition was double in the third-molar agenesis group than in the normal group. Statistically significant correlation was established between third molar agenesis and reduced number of other teeth or delayed formation and eruption of other permanent teeth.